Azimuthal stability of trichel pulses and cathode directed streamers - Bolotov, O.; Kadolin, B.; Mankovskyi, S.; Ostroushko, V.; Pashchenko, I.; Taran, G.; Zavada, L. (Вопросы атомной науки и техники, 2019)
The numerical simulations of negative corona discharge in Trichel pulse mode are carried out with the calculation of evolution of azimuthal perturbations. It is found the azimuthal instability with increment corresponding to avalanche development. This instability is suppressed at the nonlinear stage and does not lead to the process branching. The result is also applicable to the azimuthal instability of the cathode directed streamer, found earlier. The difference in their increments is followed from the difference in courses of the processess, which is discussed. Виконане числове моделювання негативної корони в режимі імпульсів Тричела з розрахунком еволюції азимутальних збурень. Виявлено азимутальну нестійкість з інкрементом, відповідним розвитку лавини. Ця нестійкість пригнічується на нелінійній стадії і не веде до галуження процесу. Результат також застосовується до виявленої раніше азимутальної нестійкості спрямованого до катода стримера. Різниця в їхніх інкрементах випливає з різниці в ході процесів, які обговорюються. Выполнено численное моделирование отрицательной короны в режиме импульсов Тричела с расчетом эволюции азимутальных возмущений. Выявлена азимутальная неустойчивость с инкрементом, соответствующим развитию лавины. Эта неустойчивость подавляется на нелинейной стадии и не ведет к ветвлению процесса. Результат также применим к выявленной ранее азимутальной неустойчивости направленного к катоду стримера. Разница в их инкрементах следует из разницы в ходе процессов, которые обсуждаются.